2012
DOI: 10.1038/tp.2012.99
|View full text |Cite
|
Sign up to set email alerts
|

Using a pharmacogenomic algorithm to guide the treatment of depression

Abstract: The objective of this study was to evaluate the potential benefit of utilizing a pharmacogenomic testing report to guide the selection and dosing of psychotropic medications in an outpatient psychiatric practice. The non-randomized, open label, prospective cohort study was conducted from September 2009 to July 2010. In the first cohort, depressed patients were treated without the benefit of pharmacogenomic testing (the unguided group). A DNA sample was obtained from patients in the unguided group, but the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
147
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(152 citation statements)
references
References 22 publications
3
147
1
1
Order By: Relevance
“…These include the assessment of drug metabolizer status and inclusion of other pharmacodynamics genes with promising findings showing superiority to treatment as usual. 176 Those tests are still relatively expensive and need to be improved by adding more gene variants. They also need to be implemented in ways that allow their use in clinical routine (that is, rapid processing and convenient costs), and physicians need to learn how to use their results in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…These include the assessment of drug metabolizer status and inclusion of other pharmacodynamics genes with promising findings showing superiority to treatment as usual. 176 Those tests are still relatively expensive and need to be improved by adding more gene variants. They also need to be implemented in ways that allow their use in clinical routine (that is, rapid processing and convenient costs), and physicians need to learn how to use their results in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the composite phenotype measured for each patient, the GeneSight test generates a report that provides prescribing options for 99% of all FDA-approved antidepressant and antipsychotic drugs used to treat depression. The test has predicted health care utilizations [10] and antidepressant outcomes [11,12,13] of patients with major depressive disorder, and does so with a precision that exceeds traditional pharmacogenomic associations based on single allelic variants [14]. …”
Section: Introductionmentioning
confidence: 99%
“…An 8-week open study of 44 patients assigned in a nonrandom manner to treatment guided by the composite report (guided treatment) or nonguided treatment by the same clinicians, who were involved with the product, reported that patients in the guided group were less likely to receive medications in the ‘use with caution and with more frequent monitoring' category, presumably because of reluctance by the guided clinicians to prescribe medications that required more monitoring [47]. Although improvement of depression was similar for the first 4 weeks in both groups, a single measure at 8 weeks indicated increased depression scores for the nonguided but not the guided group.…”
Section: Prospective Treatment Studiesmentioning
confidence: 99%